2017
DOI: 10.18585/inabj.v9i3.334
|View full text |Cite
|
Sign up to set email alerts
|

Caspase Inhibitor Diminishes Caffeic Acid-induced Apoptosis in Osteosarcoma Cells

Abstract: B ACKGROUND:Caffeic acid has been shown to induce apoptosis in MG63 osteosarcoma cells. Along with the apoptotic induction, caffeic acid was shown to activate caspase-8, -9 and -3. However, the role of caspase in mediating caffeic acid-induced apoptosis in MG63 cells are not clear yet. In this study, caspase role was further investigated by inhibiting caspase activity in the caffeic acid-induced apoptosis system in the MG63 cells. METHODS:MG63 cells were cultured, starved, pretreated with/without Z-VAD FMK and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 16 publications
1
9
0
Order By: Relevance
“…(20) Previous studies have reported that caffeic acid induced apoptosis in MG-63 osteosarcoma cells via caspases activation. (21,22) Crosstalk between the extrinsic and intrinsic apoptotic pathway involves the cleavage of BH3-interacting death (Bid) to form truncated Bid (t-Bid). t-Bid enter the mitochondria and cause cytochrome c (Cyt c) release from mitochondria to cytosol.…”
Section: Introductionmentioning
confidence: 99%
“…(20) Previous studies have reported that caffeic acid induced apoptosis in MG-63 osteosarcoma cells via caspases activation. (21,22) Crosstalk between the extrinsic and intrinsic apoptotic pathway involves the cleavage of BH3-interacting death (Bid) to form truncated Bid (t-Bid). t-Bid enter the mitochondria and cause cytochrome c (Cyt c) release from mitochondria to cytosol.…”
Section: Introductionmentioning
confidence: 99%
“…(3,(5)(6)(7)14) Caffeic acid activated the Caspases, further inducing osteosarcoma cells into apoptosis. (15,16) Meanwhile, in bone resorption, caffeic acid has a potential in inhibiting RANKL-TNFainduced osteoclastogenesis through TRAF6, p38 MAPK, JNK/SAPK, Nuclear Factor of Activated T-cells cytoplasmic 1 (NFATc1), and NFkB. (3,5-7) However, potential of the caffeic acid in other important osteoclastogenic signaling pathways, such as p44/42 MAPK (17) and Akt (18), have not been known.…”
Section: Rankl and Tnfα-induced Phosphorylation Of Akt At Ser473 And Thr308 Was Not Inhibited By Caffeic Acidmentioning
confidence: 99%
“…(9) Caspase 3 and its family have been widely investigated as the target for inducing apoptosis in tumor cells. (10)(11)(12) Addition of RS as high amylose maize starch has been reported due to its capability in increasing apoptosis and reducing proliferation of the colon cancer epithelial cell. (7) Besides that, butyric acid has anti-inflammatory effect as well, the malondialdehyde (MDA) level in plasma and colonocytes can be decreased.…”
Section: Introductionmentioning
confidence: 99%